A difusão da ideologia imperialista estadunidense nas histórias em quadrinhos dos avengers (1963 a 1967) - Pereira, Carlos Eduardo Boaretto (2013)
This dissertation is the result of research that aimed at the analysis of comic magazines of U.S. publisher Marvel Comics, The Avengers. The time frame that comprises the analysis of the magazines is from September 1963 to December 1967. This period consist into the formation of this group of superheroes (The Avengers), and the second attempt to launch a magazine with the superhero of the Second World War, Captain America, which was integrated into the group by publishers in March 1964, until the last appearance of Captain America in The Avengers magazine in the December 1967 edition. The proposal of the magazine consisted in grouping several superheroes in a single group. All the superheroes had appeared previously in other comics from this publisher. Ant-Man and Wasp in "Tales to Astonish" number 27 in January 1962. Hulk in his own magazine, "The Incredible Hulk", in May 1962; Iron Man in "Tales of Suspense" number 39, in March 1963; Thor in "Journey Into Mystery" number 83, in August 1962 and Captain America in "Captain America" number 01 in March 1941. This work has two hypotheses: The first is: the comics of superheroes Captain America and Avengers helped the project from a portion of American civil society composed by the great capitalists, and therefore, a portion of the American political society that aimed political and/or military intervention, if necessary, in other countries, to ensure raw material and consumer markets after the Second World War. And the second is: The Avengers comic books also served to minimize and even disqualify radical movements for civil rights, which in the 1960s in the U.S., began a wave of questioning the status quo of the country, coming to cogitate the transformation of the American capitalist system